2020
DOI: 10.1177/1757975920909114
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, gender, and health: an ethnographic analysis of women in a Mumbai slum

Abstract: Objective: Quantitative studies have demonstrated that social capital can positively impact community health, but qualitative explorations of the factors mediating this relationship are lacking. Furthermore, while the world’s poor are becoming increasingly concentrated in the cities of lower-middle income countries, most of the existing literature on social capital and health explores these variables in Western or rural contexts. Even fewer studies consider the impact of social constructs like race, gender, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The literature on social support systems in slums most relevant to MNH is that focused on the role of friendship between mothers and peer educators, health workers, and/or community health workers. In Mumbai slums, social capital has been identified as crucial during health crises, allowing women to navigate complex networks of public and private clinics [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature on social support systems in slums most relevant to MNH is that focused on the role of friendship between mothers and peer educators, health workers, and/or community health workers. In Mumbai slums, social capital has been identified as crucial during health crises, allowing women to navigate complex networks of public and private clinics [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Athavale et al across the Mumbai slums amongst young mothers indicated clear knowledge of exclusive breastfeeding from healthcare providers, there was however conflicting information on family elders regarding exclusive breastfeeding [ 15 ]. The study also recorded the knowledge about hygiene and safe cooking practices which were found to be adequate as per national guidelines on young infant and child feeding practices.…”
Section: Reviewmentioning
confidence: 99%
“…Most studies reviewed have not explored the attitude toward change-making directly. However some of the responses documented in the publication hint towards factors like: for male residents of the slums, across Delhi [ 14 ] and Mumbai [ 15 ], the quick service provisions were the key factor in shifting across various healthcare providers, they prefer shorter waiting times and medicines that can assure quicker recovery, thus the confidence of a healthcare provider also accounts to change making determinants. In the case of older residents closeness to the healthcare provider was a key factor in change-making, they preferred to change to the closest healthcare provider while relaxing on cost and waiting time.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mumbai slums, social capital has been identified as crucial during health crises, allowing women to navigate complex networks of public and private clinics. 22 Despite this positive association, much of the literature shows that women in slums often have weak and unreliable networks, described as fragile, non-existent, and incubators of misconceptions and poor practices -especially around newborn health and family planning. 23,24,25,26 Key informants confirmed that women in urban slums are vulnerable in ways that they are not when surrounded by family and community in rural areas, including being more easily victimized, and without a strong sense of support (Participant 2, personal communication, January 12, 2016; Participant 4, personal communication, March 2, 2016).…”
Section: Urban Power Structures Are Complex and Ever Changingmentioning
confidence: 99%